2015
DOI: 10.1016/j.jbiomech.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring microscale strain fields in articular cartilage during rapid impact reveals thresholds for chondrocyte death and a protective role for the superficial layer

Abstract: Articular cartilage is a heterogeneous soft tissue that dissipates and distributes loads in mammalian joints. Though robust, cartilage is susceptible to damage from loading at high rates or magnitudes. Such injurious loads have been implicated in degenerative changes, including chronic osteoarthritis (OA), which remains a leading cause of disability in developed nations. Despite decades of research, mechanisms of OA initiation after trauma remain poorly understood. Indeed, although bulk cartilage mechanics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 57 publications
5
50
0
Order By: Relevance
“…This reductionist approach allows investigators to gain new insight into the cartilage‐specific contributions to PTOA ex vivo, investigate mechanical thresholds for peracute cellular and subcellular responses to cartilage injury, and test targeted drugs to prevent PTOA in animal models. For example, a recent study examined microscale mechanics and corresponding chondrocyte death in articular cartilage following rapid impact injury . This new technique revealed that chondrocyte death is highly correlated with a threshold of 8% microscale strain.…”
Section: Considerations For Development Of New Preclinical Models Of mentioning
confidence: 99%
See 1 more Smart Citation
“…This reductionist approach allows investigators to gain new insight into the cartilage‐specific contributions to PTOA ex vivo, investigate mechanical thresholds for peracute cellular and subcellular responses to cartilage injury, and test targeted drugs to prevent PTOA in animal models. For example, a recent study examined microscale mechanics and corresponding chondrocyte death in articular cartilage following rapid impact injury . This new technique revealed that chondrocyte death is highly correlated with a threshold of 8% microscale strain.…”
Section: Considerations For Development Of New Preclinical Models Of mentioning
confidence: 99%
“…When the superficial layer of the cartilage was removed, cell death penetrated deeper into the cartilage, indicating a protective role for the superficial layer. Additionally, chondrocyte death developed within 2 h of impact, suggesting a narrow window for early therapeutic intervention after injury . In summary, an overly aggressive model with rapid progression to end‐stage OA may not provide a sufficiently dynamic range of disease to evaluate therapeutic effects in a preclinical ankle model and a single, rapid impact model is most consistent with the likely etiopathogenesis of ankle PTOA.…”
Section: Considerations For Development Of New Preclinical Models Of mentioning
confidence: 99%
“…For such models, the assumption of continuous attachment between chondrocytes and their environment could also be updated to discrete focal cell‐matrix attachment sites . Direct validation of chondrocyte strains in the cartilage ECM have yet to be performed and may become more feasible in the near future with new developments in the field . Finally, we focused on analyzing the micromechanical environment of chondrocytes located in the middle zone of the cartilage under unconfined compression.…”
Section: Discussionmentioning
confidence: 99%
“…49 Direct validation of chondrocyte strains in the cartilage ECM have yet to be performed and may become more feasible in the near future with new developments in the field. 50 Finally, we focused on analyzing the micromechanical environment of chondrocytes located in the middle zone of the cartilage under unconfined compression. Given the depth-varying non-homogeneous strain field that was induced in both healthy and OA conditions, the effects of depth-wise variations in the chondrocyte shapes and PCM thickness and properties on chondrocyte deformations should be accounted for in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…While this initially may seem biologically insignificant, it has to be considered that the baseline expression of chondrogenic marker genes of human chondrocytes in free swelling GelMA-HAMA constructs is already high. to chondrocyte death due to excessive magnitudes of mechanical stresses and strains [349], as well as high stress and strain rates in response to impact-loading [350].…”
Section: Effects Of Preculture and Loading On Chondrocyte Gene Expresmentioning
confidence: 99%